Post COVID-19 Stress and Anxiety Levels Among Undergraduates at a Tertiary Care Hospital, Pondicherry - Joe David Anton J; Ramasamy R; Manivarma R.K.; Karthick S; Sabaresh Pandiyan (National Board of Examinations Journal of Medical Sciences)
Background: Stress, Anxiety and Depression are threat indicators which debilitates an individual’s life span. These stressors are often undiagnosed or misdiagnosed due to which the person does not know the prevalence of them in his / her own life. Materials & Methods: The study was conducted with total of 379 medical students participated in the Department of Forensic Medicine and Toxicology, Mahatma Gandhi Medical College and Research Institute, Puducherry with a self – designed questionnaire mailed as Google Form. The study tool used in this study Peritraumatic Distress Inventory (PDI) and Zung Self - rating Anxiety Scale. The data analyzed and the results were automated accordingly. Results: A total of 205 MBBS students participated in the study. Nearly half of the sample had undergone self-quarantine (51.2%). Most of the students had relatives quarantined during the pandemic (68.8%) and were treated for COVID symptoms (68.8%). Peri-traumatic distress was greater among students with self-quarantine history or relative being quarantined, and history of treatment for self or relative for COVID symptoms than students without such history. Conclusion: The findings of this study underscore the significant psychological impact of the COVID-19 pandemic on medical undergraduate students, particularly in those who experienced personal or familial exposure to treatment or quarantine.